PENGARUH PENGALAMAN PELANGGAN DAN PERSEPSI HARGA TERHADAP KEPUASAN SERTA DAMPAKNYA TERHADAP LOYALITAS KONSUMEN: (Studi Pada Pengguna E-Commerce Shopee Di Kota Semarang) - Syach, Zein Zidane; Tjahjaningsih, Endang (Politeknik Negeri Ambon, 2025)
Introduction: Shopee holds the position as the leading e-commerce platform in Indonesia, primarily due to its aggressive promotional strategies, extensive product variety, and appealing pricing schemes. Despite its dominance, several factors still hinder user satisfaction and retention. These include a complex and heavy app interface, frequent delivery delays, and discrepancies between the product description and the actual items received. Moreover, additional charges such as handling fees and shipping costs are often seen as excessive during the checkout process. Given these ongoing concerns, this study aims to explore the impact of user experience and price perception on customer satisfaction and loyalty among Shopee users in Semarang City Methods: This study employs a quantitative research approach. Data were gathered through an online questionnaire distributed via Google Forms, targeting 109 respondents selected through purposive sampling. The analysis involved various statistical tests, including validity and reliability assessments, multiple linear regression, coefficient of determination test, F-tests, and hypothesis testing. The data were processed using SPSS 23Results: The findings reveal that user experience plays a significant role in shaping customer satisfaction levels. Furthermore, satisfaction was found to have a strong influence on user loyalty. From these outcomes, it can be inferred that providing a seamless and consistent user experience is crucial for fostering long-term loyalty among Shopee users in Semarang. Although Shopee offers a competitive pricing process aligned with costs incurred, users do not view pricing as the primary driver of their continued use of the platform. Keyword: Customer Experience, Price, Satisfaction, Loyalty